English and ethnicity - Brutt-Griffler, Janina, 1966-; Davies, Catherine Evans (Signs of race., 2006)
English and Ethnicity offers a scholarly but accessible exploration of the complex interaction between the English language and the (de) construction of ethnicity. Centered in applied (socio) linguistics, the volume?s diverse essays demonstrate that the constructs of both English and ethnicity are contested sites of identity formation in the English- speaking world. They illustrate that while for some English use indexes ethnicity, for others its usage involves equally significant processes of de-ethnicization. English and Ethnicity enriches our understanding of the contemporary dialogue on heritage languages, language policy, and language maintenance.